THORACOMELIA IN A LAMB - Veeraiah, G; Srinivas, Manda; Rani, N Lakshmi (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Polymelia refers to additional limbs and the condition is further classified based on location as thoracomelia when the duplicated limbs are attached to the thorax, occurrence of these conditions in sheep is very rare (George, 2002). The present communication places on record a case of double thoracomelia in a female lamb.